Quality in Anthurium andraeanum after postharvest BAP treatment - Favero, B. T. [UNESP]; Lima, G. P.P. [UNESP]; Cavasini, R. [UNESP]; Laschi, D. [UNESP] (International Society for Horticultural Science (ISHS), 2015)
To ensure the ongoing quality of anthurium inflorescence it is necessary to use postharvest treatments aimed at extending the vase life and delaying senescence. Thus, the objective of this study was to assess the effect of postharvest spray application of 6-benzylaminopurine (BAP) in anthurium quality and sugar levels. Two experiments were done, one where inflorescences were sprayed 0, 100 and 200 mg L-1 of BAP and kept under 23±1°C and relative humidity of 65±5% for evaluations, and in the second experiment BAP concentrations were reduced to 0, 50 and 100 mg L-1 and inflorescences were cold stored for 2 days at 13±1°C and then transferred to the same evaluation conditions from the first experiment. Quality assessments were performed according to Paull (1982) for spathe loss of gloss and blueing and spadix necrosis along with stem weighting for fresh weight (FW) variation every two days. In the first experiment FW loss was significantly lower from the 14th until 26th day after harvest. Anthurium sprayed with 100 and 200 mg L-1 showed significantly less fresh weight loss when compared to control stems and in the second experiment 50 and 100 mg L-1 did not reduce fresh weight loss. Means of scores from quality analysis, blueing and loss of gloss of spathes and spadix necrosis, were significantly lower in BAP sprayed anthurium (100 and 200 mg L-1) than in control flowers and by lowering BAP spray concentration and cold storing stems for two days this positive effect was only observed for spadix necrosis and not observed for spathe parameters.
Keywords: Biochemistry; Cytokinin; Spray